A pair of linear canonical Hankel transformations and associated pseudo-differential operators. Issue 15 (18th November 2018) - Prasad, Akhilesh; Kumar, Tanuj
Abstract: In this work, we have introduced a pair of linear canonical Hankel transformations and investigated some of its properties on Zemanian-type spaces. Moreover two versions of pseudo-differential operator associated with canonical Hankel transformations are defined and discussed its integral representation.